Neuroprotective Effects of Butanol Fraction of Cordyceps cicadae on Glutamate‐Induced Damage in PC12 Cells Involving Oxidative Toxicity. Issue 1 (27th December 2017) - Wang, Dan; Wang, Jibiao; Wang, Dujun; Yu, Xiaofeng; Olatunji, Opeyemi Joshua; Ouyang, Zhen; Wei, Yuan
Abstract : The current study was aimed at investigating the neuroprotective effects of the butanol fraction from Cordyceps cicadae (CBU ), which was responsible for the anti‐aging effect of this medicine. Glutamate‐induced PC12 cells were used as a model to determine the neuroprotective effect against oxidative cell death. Cell viability, cytotoxicity, flow cytometry, mitochondrial transmembrane potential (MMP), reactive oxygen species (ROS), glutathione peroxidase (GSH‐Px), and superoxide dismutase (SOD) levels were analyzed to assess neuronal cell survival or death. The results obtained from the above evaluations showed that CBU was the most effective fraction and even better than pure compounds present in C .  cicadae in terms of suppressing glutamate‐induced damage in PC12 cells, increasing cell viability, decreasing lactase dehydrogenase (LDH) release, and reduction of apoptosis induced by exposure to glutamate. Furthermore, CBU protected cells against mitochondrial dysfunction and oxidative stress as indicated by the suppression of ROS accumulation and up regulation of the levels of GSH‐Px and SOD. In summary, the above results showed that CBU exerted neuroprotective effect against oxidative damage, and this activity could be partly due to the action of nucleosides present in the CBU . Abstract :